The Role of the SIKSDA Application (Regional Financial Information System) in Enhancing the Efficiency of Financial Recording and Reporting in Sidoarjo Regency - Novita Nindya Rakhmadewi; Kristyan Dwijosusilo; Kresna Adhi Prahmana (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study examines the role of the Regional Financial Information System application (SIKSDA) in improving the efficiency of financial recording and reporting in Sidoarjo Regency, East Java. Local governments are increasingly required to manage public funds quickly, accurately, and accountably, yet manual administrative practices remain a source of recording errors and reporting delays. Using a descriptive qualitative approach, data were collected through semi-structured interviews with staff of the Regional Financial and Asset Management Agency (BPKAD), direct observation of the system in use, and analysis of related budget and reporting documents. The findings indicate that SIKSDA shortens the financial recording cycle by automating transaction entry, integrating data across regional work units, and minimising duplication and arithmetic errors that previously occurred in manual bookkeeping. In the reporting dimension, the system accelerates the preparation of accountability reports, enables real-time monitoring of budget realisation, and improves the consistency between planning, execution, and reporting documents, thereby strengthening transparency and accountability. Nevertheless, the efficiency gains are not yet optimal because of limited technically skilled human resources, uneven supporting infrastructure, and the persistence of manual work habits. The study concludes that SIKSDA functions not merely as an administrative tool but as a strategic instrument of good public financial governance. It recommends continuous training, strengthening of technical infrastructure, and bureaucratic reform so that the efficiency potential of the system can be fully realised. The novelty of this study lies in its specific focus on recording and reporting efficiency at the operational level of a single regency, complementing prior research that emphasises transparency and accountability more broadly.